2020
DOI: 10.3390/en13205353
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Efficient Polymer Electrolyte Membrane Fuel Cell Control Using Successive Linearization Based Model Predictive Control Validated on Real Vehicle Data

Abstract: In this paper, a polymer electrolyte membrane fuel cell (PEMFC) stack control study is presented. The goal is to track the transient power demand of a real fuel cell (FC) vehicle while ensuring safe and efficient operation. Due to the dynamically changing power demand, fast transients occur in the internal states of the fuel cell (e.g., pressure, humidity, reactant mass) leading to degradation effects (e.g., high/low membrane overpressure, reactants starvation) which are avoided by imposing safety constraints.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The difference is that the adapted model has the property of analytical differentiability, which is the reason for its selection. This property is beneficial for various control methodologies [20,21], and parameter sensitivity analyses (Section 3.2). The model is a zero-dimensional physical PEMFC model, and Figure 1 gives a schematic overview.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The difference is that the adapted model has the property of analytical differentiability, which is the reason for its selection. This property is beneficial for various control methodologies [20,21], and parameter sensitivity analyses (Section 3.2). The model is a zero-dimensional physical PEMFC model, and Figure 1 gives a schematic overview.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In the hybrid electric vehicle, the engine bay was replaced with a fuel cell system. The car is shown in Figure 2 and more information on it can be found in [29,30].…”
Section: Vehicle As Validation Data Generatormentioning
confidence: 99%
“…In this subsection, the model used for the study is briefly presented as the detailed derivation can be found in [29,30]. The model structure is shown in Figure 4.…”
Section: Plant Modelmentioning
confidence: 99%
See 2 more Smart Citations